Upaya Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Melalui Penerapan Metode Eksperimen Pada Siswa Kelas VI MIN 4 Bungo - Fatmawati Fatmawati (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT This research is a classroom action research, while the purpose of this research is to describe the increase in learning outcomes of class VI students after applying the experimental method in learning natural sciences on material properties of conductors and insulators of matter at MIN 4 Bungo. Data collected by observation, interviews and documentation. The subjects of this study were students of class VI MIN 4 Bungo, Tanah Sepenggal Lintas District, Bungo Jambi Regency, with a total of 28 students consisting of 12 male students and 16 female students. The results showed that as many as 14 students or 74% of all students scored below 60 compared to the first cycle score data which was only 10 students or 53%, while the number of students who had not completed was 5 students or 26% of all students who scored in above 70. Based on the results of observations of the attitudes of students in cycle I, it can be seen from several aspects of student attitudes consisting of: 1) students have tried to work on science problems in their own way; 2) students try to solve science problems according to the steps they have learned; 3) students try to ask questions if there is something that is not understood in science learning and 4) students try to relate science concepts to everyday life. Keywords ; learning outcomes, science, experimental methods